Environmental Assessment of the Integration of Active Solar Energy Systems on Building Envelopes in Southern Europe - Vassiliades, Constantinos; Michael, Aimilios; Savvides, Andreas L.; Kalogirou, Soteris A. (My University, 2017)
This study aims at making an environmental assessment of the integration of active solar energy systems on building envelopes in southern Europe. More specifically, it focuses on the investigation of shading and insolation of indoor spaces in relation to the energy requirements and the visual comfort of inhabitants. For the needs of the present research, five active solar systems and three representative space typologies were selected for in-depth investigation. Autodesk Ecotect Analysis software v.5.2 and Desktop Radiance v2.0 Beta were used for the simulations. The simulation results are presented and discussed comparatively. The findings indicate that the integration of active solar systems contributes to drastic reductions of the cooling and heating loads. In terms of natural lighting, the integration of active solar systems enables high levels of natural lighting, minimizes glare issues in the majority of systems. The research highlights the role of integrated active solar systems in buildings both in the indoor built environment and in energy performance.
Keywords: Environmental assessment; Active solar systems; Architectural integration; Thermal and visual comfort; Southern Europe